PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Christian Timotius Peilouw (University of Merdeka Malang, 2017)
The purpose of this study is to know the influence of stock ownership by management, stock ownership by institution, stock ownership by family, stock ownership by foreigner, and stock ownership by the government on debt policy which use agency theory, by using the variables of profitability control, company growth, company size and asset structure. The samples used were 358 companies non-bank and finance listed on BEI (Indonesia Stock Exchange) over the period of 2013-2014. The data collection technique used is the purposive sampling method. The data analysis technique used is multiple linear regression. The analysis shows that stock ownership by management negatively affects debt policy. Stock ownership by institution, stock ownership by family, stock ownership by foreigner, and stock ownership by the government do not affect the debt policy. Profitability negatively affects debt policy. Company size positively affects debt policy. Company growth and asset structure dont affect debt policy. DOI: https://doi.org/10.26905/ap.v3i1.1325